Bayang-Bayang Kolonial dan Digital : Model Dakwah Moderasi Ulama Nusantara , Tradisi, dan Ketahanan - Nafisah Azka Sabila; Awaliyah Azzahrah Ridwan; Dio Aryansyah; Aura; Abdul Fadhil (Yayasan Al-Afif, 2025)
Digitalization encourages the spread of extremism, demanding an adaptive approach to da'wah. This study aims to develop the Moderate Da'wah Communication Model of Nusantara Ulama as a response to the ideological challenges posed by Colonial Shadows and the polarization of the Digital Age. The core issue is identifying communication message traditions and strategies for da'wah resilience. This qualitative study uses literature review, analyzed through the Da'wah Communication framework. Findings show that moderation messages are rooted in Sufism and pesantren ethics, emphasizing Zuhud to control fanaticism. The main model relies on the Salaf Pesantren as an example and Kitab Kuning for message standardization, utilizing a non-confrontational approach. The study's implication is the formulation of a Communal Hybrid Communication Model based on traditional authority and deep literacy, which effectively counteracts digital extremism.